Characterisation of nano whiskers from kenaf bast and effects on bionanocomposites via solution casting - Zaini, Lukmanul Hakim (2013)
There are limited studies of isolated cellulose whiskers from kenaf bast. Kenaf bast contains less than 30% of total weight, it needs small usage but high performance – high value. Cellulose nano whiskers (CNW) can be isolated by sulphuric acid hydrolysis from kenaf bast fibres and potentially have higher strength, increase efficiency and added value compared to normal fibre. Moreover, CNW has good properties as reinforcing material in any type of composites. In this study, cellulose whiskers were isolated from kenaf (Hibiscus cannabinus L.) bast fibres via sulphuric acid hydrolysis. Raw bast kenaf, NaOH treated and bleached fibres morphology was analyzed by Field Emission Scanning Electron Microscopy (FE-SEM) while the whiskers were analyzed by Transmission Electron Microscopy (TEM). Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffractometry (X-RD), and thermogravimetric analysis (TGA) used to characterize all samples. Nanocomposites were produced by incorporating various amounts (2.5 – 10%) of resulted kenaf whiskers with Cellulose Acetate Butyrate (CAB). Resulted nanocomposites characterized by FTIR, TGA, DSC, and DMA. The TEM images showed that the sulphuric acid whiskers have average diameters and length range of 3 nm and 305 nm, respectively. The FTIR study indicated that during the conversion process, most of the hemicellulose and almost all the lignin were removed by the NaOH and subsequent bleaching treatments. The crystallinity of kenaf whiskers was 72%. It is suggested that the lower crystallinity value compared to NaOH and bleached fibres because of the acid attacked the crystalline region. Thermogravimetric analysis (TGA) indicated that a two-stage decomposition behaviour was revealed in the kenaf whiskers due to incorporation of the sulphate group with the cellulose crystals. FTIR analysis showed no intermolecular hydrogen bonding between CAB and whiskers. Thermal analysis found that whiskers reinforcement did not affect the decomposition temperature of resulted nanocomposites. However, good miscibility detected by the single decomposition temperature of nanocomposites. The addition of kenaf whiskers nanofillers did not have any effect on matrix melting temperature,recrystallization during first and second heating and cooling and glass transition temperature. It was concluded that kenaf whiskers addition did not affected the onset of translational and rotational backbone motions in the composite matrix. The dynamic mechanical improvement showed by the increment of kenaf whiskers as filler content into the CAB matrix is believed due to filler-filler interactions through hydrogen bonding.